FTIR Spectrometry with PLS Regression for Rapid TBN Determination of Worn Mineral Engine Oils - Sejkorová, Marie; Šarkan, Branislav; Veselík, Petr; Hurtová, Ivana (My University, 2020)
The TBN (Total Base Number) parameter is generally recognized by both engine oil processors and engine manufacturers as a key factor of oil quality. This is especially true for lubricating oils used in diesel and gas engines, which are exposed to relatively high temperatures and, therefore, require more effective protection against degradation. The FTIR spectrometry method together with a multivariate statistical software helped to create a model for the determination of TBN of worn motor oil SAE 15W-40 ACEA: E5/E7, API: CI-4. The best results were provided using a model FTIR with Partial Least Squares (PLS) regression in an overall range of 4000–650 cm−1 without the use of mathematical adjustments of the scanned spectra by derivation. Individual spectral information was condensed into nine principal components with linear combinations of the original absorbances at given wavenumbers that are mutually not correlated. A correlation coefficient (R) between values of TBN predicted by the FTIR-PLS model and values determined using a potentiometric titration in line with the ČSN ISO 3771 standard reached a value of 0.93. The Root Mean Square Error of Calibration (RMSEC) was determined to be 0.171 mg KOH.g−1, and the Root Mean Square Error of Prediction (RMSEP) was determined to be 0.140 mg KOH.g−1. The main advantage of the proposed FTIR-PLS model can be seen in a rapid determination and elimination of the necessity to work with dangerous chemicals. FTIR-PLS is used mainly in areas of oil analysis where the speed of analysis is often more important than high accuracy.
FTIR spektrometrie s PLS regresí pro rychlé stanovení TBN použitých minerálních motorových olejů
Keywords: oil analysis; engine oil; lubricants; FTIR spectrometry; total base number (TBN); partial least squares (PLS); analýza oleje; motorový olej; maziva; FTIR spektrometrie; číslo celkové alkality (TBN); částečné nejmenší čtverce (PLS)